2007
DOI: 10.1002/ijc.23194
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of high risk occupations for bladder cancer in New Zealand

Abstract: We conducted a nationwide case-control study of bladder cancer in adult New Zealanders to identify occupations that may contribute to the risk of bladder cancer in the New Zealand population. A total of 213 incident cases of bladder cancer (age 25-70 years) notified to the New Zealand Cancer Registry during 2003 and 2004, and 471 population controls, were interviewed face-to-face. The questionnaire collected demographic information and a full occupational history. The relative risks for bladder cancer associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
1
37
3
1
Order By: Relevance
“…Czene et al (2003) found an increased risk for urinary bladder cancer among male hairdressers which peaked with exposures back in the 1960s and has been decreasing in the following years. Gaertner et al (2004) and Dryson et al (2008) also confirmed these findings. However, in recent decades, an increased risk of bladder cancer amongst hairdressers could not be determined (Czene et al 2003).…”
Section: Introductionsupporting
confidence: 89%
“…Czene et al (2003) found an increased risk for urinary bladder cancer among male hairdressers which peaked with exposures back in the 1960s and has been decreasing in the following years. Gaertner et al (2004) and Dryson et al (2008) also confirmed these findings. However, in recent decades, an increased risk of bladder cancer amongst hairdressers could not be determined (Czene et al 2003).…”
Section: Introductionsupporting
confidence: 89%
“…Hairdressing was identified as one of the highest risk occupations of bladder cancer because of the exposure to dye [9,34,35]. In this study no significant association was identified between them.…”
Section: Discussioncontrasting
confidence: 45%
“…*Two studies26 41 were excluded because study period was not presented in the original study.†Two studies from New Zealand35 55 were excluded from this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…† For convenience reasons only the first author is given. Studies 17 18 26 33 35 37 41 42 44–48 51 52 55 56 with no definition or unsuitable definition for job held were excluded form this analysis.…”
Section: Resultsmentioning
confidence: 99%